Design of an Off-Grid Solar PV System for a Renewable Energy-Based Home in Bengkulu - Reza Satria Rinaldi; Afriyastuti Herawati; Ika Novia Anggraini; Helmizar Helmizar (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2025)
Bengkulu Province has a solar energy potential of 3,475 MW, with an average daily solar irradiance duration of 5.9 hours in 2022 and 8.3 hours in 2023. This study designs an off-grid solar PV system for a renewable energy-based home (REH) model in the coastal area of Bengkulu City. The REH is a home with electrical energy independence that utilizes renewable energy systems to generate electricity. This study focuses on the REH powered by solar energy, intended for a modest home with a power capacity equivalent to a 900 VA PLN customer classification. The data on solar energy potential in the coastal area of ​​Bengkulu City used in this study is from the Global Solar Atlas. The data analysis confirmed the need for the REH model to generate electricity from solar energy, requiring 12 units of 120Wp PV modules in a PV array. An appropriate solar charge controller for this REH model is the MPPT SCC with a rating of 48 V 30 A. Based on the selected PV modules and the daily load of the REH model, the required 48 V battery capacity is 300 Ah, and the PSW Inverter 2,000 VA 48 V.